The relationship between urban heat island and air pollutants and them with influencing factors in the Yangtze River Delta, China - Wang, Yuanyuan; Guo, Zhongyang; Han, Ji (Ecological indicators, 2021)
•There was a great spaito-temporal differences in UHI and air pollution in the YRD.•There was a positive correlation between surface UHI and O3 pollution in the YRD.•Vegetation has a good cooling LST and dust removal function in urban area.•The natural and human factors collectively influence on UHI and air pollutants. The relationship between urban heat island (UHI) and air pollution is worth exploring. We used land surface temperature (LST) and air quality data investigated the spatio-temporal distribution of UHI intensity (UHII) and six air pollutants of carbon monoxide (CO), nitrogen dioxide (NO2), ozone (O3), fine particle matter (PM2.5), coarse particle matter (PM10) and sulfur dioxide (SO2) in the YRD during 2015–2019, and the correlation relationship between UHII and air pollutants concentration. Using regression analysis to analyze the influence of natural and human factors on the UHI and air pollutants. We found that: (1) Annual average daytime UHII was 1.20 ℃ and northern higher than southern cities. Nighttime UHII was 0.35 ℃ and southern higher than northern. Annual average CO, NO2, O3, PM2.5, PM10 and SO2 concentrations were 0.83 mg/m3, 35.41 ug/m3, 63.34 ug/m3, 44.16 ug/m3, 73.46 ug/m3, 13.86 ug/m3, respectively. Air pollution in inland cities were worse than coastal cities. (2) A significant positive correlation between daytime UHII and O3 concentration, and a negative correlation with other pollutants. (3) The influence of LST is the closest factors, followed by vegetation coverage, geographic location, elevation and economic development intensity on UHII and air pollution.